STUDY OF PHOTOCURRENT ENHANCEMENT THROUGH PLASMON RESONANCE EFFECTS OF METAL NANOPARTICLES IN ORGANIC-INORGANIC HYBRID SOLAR CELLS - Cikal Merdeka, Muhammad
Organic solar cells are currently one of the most popular researches related to renewable energy because the devices are lighter, more flexible, cheaper to produce, and relatively easy to manufacture in comparison to solar cells with inorganic semiconductor crystalline materials. Various solar cell structures have been developed either by using organic-inorganic hybrids, donor-acceptor blends in bulk heterojunction structures, or using inverted configurations in an effort to improve the performance efficiency of the device. However, there are still many study for the development of organic solar cells in dealing with the problems of low efficiency and stability of the device that comes from the photocurrent generation mechanism in the structure of organic solar cells. In this study, we investigate the mechanism of charge carrier generation and their transport process in hybrid bulk heterojunction solar cell with an inverted structure by utilizing the localized surface plasmon resonance (LSPR) effect of gold nanoparticles. Incorporation of gold nanoparticles in this study was carried out into ZnO layer as an electron transport layer (ETL) in order to increase light absorption in the active layer and increase the transpor process of charger carriers at the interface between the active layer and ETL . The synthesis of gold nanoparticles capped by 3-mercaptopropionic acid (AuMPA) was carried out by reduction process following the method of Yonezawa and Kunitake et. al (1999) with a slight modification of the gold precursor and citrate concentration following our previous study (Pambudi et al, 2022) and synthesis of gold nanoparticles capped by oleylamine was carried out by following the method of Hiramatsu dan Osterloh et.al (2004). The fabrication of solar cells with the structure of ITO/ZnO:AuNP/P3HT:PCBM/PEDOT:PSS/Ag was carried out using spin coating and thermal evaporation techniques. Furthermore, the formation of AuMPA was characterized by UV-Vis and FT-IR spectroscopy, while the performance of the solar cell device was tested by measuring current-voltage (J-V) equipped with a 1.5G AM solar simulator. The results of UV-Vis characterization show the plasmonic peak of the absorbance spectrum of the AuMPA solution at ~527 nm and the particle has a spherical shape with diameter size of 51 nm as indicated by the TEM and PSA results. While the AuOA solution shows a plasmonic peak at a wavelength of ~530 nm with diameter size of 12 nm. The incorporation of AuMPA into ZnAc solution was stable enough for AuMPA concentration in ZnAc less than 2,65 wt% and the addition of AuOA was quite stable up to a concentration of 3.53 wt%. The results of the solar cell fabrication show an increase in the current density under short circuit conditions (Jsc) from 46.7 mA/????????2 to 83.1 mA/????????2 and an increase in the value of open circuit voltage (Voc) from 0.42 V became 0.43 V with the addition of 1.77 wt% AuMPA in ZnAc solution along with an increase in power conversion efficiency (PCE) from 5.64 % to 9.00 % as shown by J-V measurements. In the case of the addition of AuOA about 2.65 wt%, the solar cell device shows the enhancement of performance with the Jsc value of 22.7 mA/????????2 to 44.1 mA/????????2 and the Voc of 0.40 V to 0.46 V along with increase efficiency from 2.71 % to 5.32 %.